Optimizing Pulse Productivity through Phenological Assessment and Stingless Bee Pollination in Gondia District, Maharashtra - Ramkrushna Bhelawe; Ashish Kumar Jha; Jagruti Roy; Shreya Ghonmode; Rewati Acharya; Syed Obaid Qureshi; Mrunal. C. Kale (The Bioscan, 2025)
Pulses are a cornerstone of Indian agriculture, valued for their nutritional contribution, nitrogen fixation, and adaptability to rainfed systems. Despite their importance, pulse yields remain constrained by pollination deficits and seasonal variability. This study documents the phenological diversity of major pulse crops in Gondia District, Maharashtra, and evaluates the effect of stingless bee (Tetragonula pagdeni) pollination on crop productivity. Phenological observations of ten pulse species—Cajanus cajan, Cicer arietinum, Vigna radiata, Vigna mungo, Vigna unguiculata, Cyamopsis tetragonoloba, Vicia faba, Pisum sativum, Glycine max, and Lathyrus sativus—were recorded across Kharif, Rabi, and late Rabi seasons. Field experiments compared open pollination with bee-assisted pollination treatments, measuring pods per plant, seeds per pod, pod weight, and 100-seed weight. Statistical analysis using Welch’s t-test revealed significant yield enhancements in most crops under stingless bee pollination, including increases in pod number (e.g., C. cajan: 244.6 ± 10.02 to 289.4 ± 12.31, p < 0.001), pod weight (P. sativum: 4.26 ± 0.93 g to 6.78 ± 1.85 g, p < 0.05), and 100-seed weight (G. max: 18.98 ± 1.00 g to 28.66 ± 0.72 g, p < 0.001). While seed number per pod showed variable responses, overall yield quality and quantity improved consistently, with notable enhancements in seed size, viability, and uniformity. These findings highlight the dual agronomic and ecological benefits of stingless bee pollination in pulses, demonstrating its potential to stabilize crop performance, increase farmer returns, and strengthen food security. The integration of T. pagdeni into pulse-based agroecosystems offers a sustainable strategy to address pollination deficits and enhance agricultural resilience in semi-arid and rainfed regions. KEYWORDS: Case report, Alopecia Areata, Autoimmune, Homoeopathy, Pix Liquida, SALT score.